Sleep-Breath–Related Characteristics in Males With Chronic Rhinosinusitis - Wenjun Xue; Qianqian Zhang; Xiaolin Wu; Huaming Zhu; Xinyi Li; Yunhai Feng; Haibo Ye (International Journal of Clinical Practice)
Conclusions: Male inpatients with CRSsNP exhibited a high prevalence of OSA. CRSsNP patients evidenced severe hypoxia and exhibited more awakenings during sleep.